Adam accepts offer to join elite sport schools - Jaafar, Arfandi (Borneo Post (KK), 2014)
KOTA KINABALU: Joining the ranks of Malaysia's top brass has been a long time coming for Sabahan archer, Adam Wong.The 18-year-old Malaysia Games (Sukma) champion is bound for training in Bukit Jalil.Come next week, his rank as national reserve would have been relinquished after he puts pen to paper as a national elite.